B-mode ultrasound and contrast-enhanced ultrasound (CEUS) of histological confirmed omental lesions: retrospective analysis of n = 44 patients - Trenker, Corinna; Dietrich, Christoph F.; Ziegler, Elena; Neesse, Albrecht; Görg, Christian (Zeitschrift für Gastroenterologie, 2019)
Introduction Little is known about the imaging of omental pathologies. The aim of the current study was to determine the value of B-mode ultrasound (B-US), contrast-enhanced ultrasound (CEUS), and ultrasound-guided core needle biopsy for the differential diagnosis of benign and malignant omental pathologies.Patients and methods A retrospective evaluation (2008–2017) was performed in 44 patients (median 65,5 years, mean 64 years [47–83], 27 male, 17 female) with histological (40/44 [91 %]) or cytological (4/44 [9 %]) proven omental lesions. Clinical signs and final diagnosis, size, B-US and CEUS findings, and complications were analyzed.Results Omental thickening was in n = 36 (81.8 %) of the cases malignant (mOL) and in n = 8 (18.2 %) benign (bOL). Twenty-six (59.1 %) patients had ascites (n = 24 [66.7 %] mOL, n = 2 [25 %] bOL). The average tumor thickness was 23 mm (24 mm in mOL, 20 mm in bOL). Interventional complications were not observed.Discussion The majority of omental lesions are malignant. The differentiation between a malignant or benign cause of thickening is not possible by any imaging method. CEUS is helpful to determine vital tissue before biopsy. Ultrasound-guided core-needle biopsy allows final diagnosis of omental thickening if > 10 mm and should be performed prior to the more invasive and complicative diagnostic laparoscopy.
Keywords: CEUS; ultrasound; omentum; omental lesion